Class Struggle or Embedded Markets? Marx, Polanyi and the Meanings and Possibilities of Social Transformation - Selwyn, Benjamin; Miyamura, Satoshi (New Political Economy, 2014)
Marx and Polanyi both held that socialism, in one form or another, was a preferable and possible alternative to capitalism. Their ideas are seen to offer theoretical tools to understand the tensions and contradictions of capitalism, and to inform ways to overcome them. This paper discusses Polanyi's work from a Marxist perspective in order to illuminate his strengths and weaknesses. Its main focus is to discuss Polanyi's juxtaposing of commodification against exploitation, in diagnosing the problems of capitalist expansion. We suggest that by juxtaposing these two moments, Polanyi not only misses out on a crucial arena of capitalist activity (exploitation), but also undermines his own explication of processes of commodification. This has deleterious consequences for his understanding of the prevalence of poverty under capitalism. It also means that his vision of social transformation and of socialism is profoundly different, and potentially antithetical, to that of Marx. We suggest that for Polanyi's conception of de-commodification to gain greater traction it needs to be combined with Marx's analysis of exploitation and class struggle.
Political Science; Economics
Keywords: MARX; Karl; 1818-1883; Polanyi; commodification; exploitation; historical materialism; institutionalism